2022
DOI: 10.1186/s43058-022-00330-1
|View full text |Cite
|
Sign up to set email alerts
|

Using decision analysis to support implementation planning in research and practice

Abstract: Background The process of implementing evidence-based interventions, programs, and policies is difficult and complex. Planning for implementation is critical and likely plays a key role in the long-term impact and sustainability of interventions in practice. However, implementation planning is also difficult. Implementors must choose what to implement and how best to implement it, and each choice has costs and consequences to consider. As a step towards supporting structured and organized imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
(168 reference statements)
1
7
0
Order By: Relevance
“…Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process. This is consistent with the work of Smith et al, who suggest that insufficient support and/or objective misalignment with stakeholder needs would threaten sustainment 66 . As a result, the likelihood of sustaining the shared sustainability objectives may be greater.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process. This is consistent with the work of Smith et al, who suggest that insufficient support and/or objective misalignment with stakeholder needs would threaten sustainment 66 . As a result, the likelihood of sustaining the shared sustainability objectives may be greater.…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, these objectives addressed all stakeholders' needs in the MPAI‐4 project. That is, they are shared objectives that the team has and will continue to unite behind over the long‐term 66 because they will continue to result in more usable knowledge and tangible outcomes for all stakeholders 67–69 . Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 In addition to effectiveness, complex implementation adoption and expansion decisions are also influenced by the costs of implementation and sustainment. [11][12][13][14][15] Best practices and guidance for assessing EBP implementation costs are emerging; 12,13,[16][17][18][19][20][21][22][23] key best practices include considering implementation costs (eg, related to implementation strategies) and EBP costs (eg, time of providers to deliver EBP), disaggregating costs across time and categories when possible, being attentive to context, and conducting sensitivity analyses. 12,19 Most existing economic evaluations of clinic-based, behavioral pediatric weight management programs pay limited attention to implementation costs compared with EBP costs and downstream health care costs.…”
mentioning
confidence: 99%
“…Future work should build from this base to include more concrete discussions of how assumptions, and their potential violations, might impact results, and should be specific about the strength of parameter estimate(s) used. Including these details is important both to establish confidence in modeled results (e.g., if there are concerns about the causal strength or appropriateness of parameter estimates used) [ 106 ] and to help policymakers understand what to expect under different implementation scenarios [ 107 ]. For example, included studies evaluating excise tax policies often assumed a 100% pass-through rate in their primary models and examined results assuming alternative rates in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%